An analysis of culture shock on students’ cultural adjustment at UIN Malang - Damayanti, Amalia Firda (Maliki Interdisciplinary Journal, 2024)
This descriptive qualitative research aims to find out the culture shock experienced by students outside Malang and how they provide solutions to the culture shock they face. The theory applied is Littlejohn's theory (2004; Kingsley and Dakhari, 2006; Balmer, 2009). Cultural shocks were also experienced by foreign student islands. Most of them experience symptoms of culture shock in several phases. This is because of the emotional state that engulfs everyone when he or she enters a different culture. The steps taken by the researcher First Determine the theme or topic of the interview. Second, compiling a list or outline of questions to be asked to the resource persons (5W+1H). Third, Determining the source persons and knowing their identities. Fourth, conducting interviews with sources. Fifth, record the main points of the interview. Sixth, Compile a report on the results of the interview. This study concludes that almost all of the interviewed respondents experienced culture shock when they just lived in Malang.